Dissemination of multi-resistant Gram-negative bacteria into German wastewater and surface waters. Issue 5 (6th April 2018) - Müller, Heike; Sib, Esther; Gajdiss, Mike; Klanke, Ursula; Lenz-Plet, Franziska; Barabasch, Vanessa; Albert, Cathrin; Schallenberg, Anna; Timm, Christian; Zacharias, Nicole; Schmithausen, Ricarda Maria; Engelhart, Steffen; et al.
Abstract: Carbapenem antibiotics constitute the mainstay therapy of nosocomial infections with extended spectrum beta-lactamase producing Gram-negative bacteria; however, resistance against these compounds is increasing. This study was designed to demonstrate that carbapenemase-producing bacteria are disseminated from hospitals into the environment. To this end, resistant bacteria were isolated from a clinical/urban and from a rural catchment system in Germany in 2016/17. The study followed the dissemination of resistant bacteria from the wastewater through the wastewater treatment plant (WWTP) into the receiving surface waters. The bacteria were cultivated on selective agar and characterized by antibiotic testing, real-time PCR targeting carbapenemase genes and typing. Bacteria with resistance to third generation cephalosporins were isolated from all sample sites. 134 isolates harboring carbapenemase genes encoding VIM, NDM and OXA-48 and 26 XDR (extensively drug-resistant) strains with susceptibility to only one or two antibiotics were isolated from the clinical/urban system. The rural system yielded eight carbapenemase producers and no XDR strains. In conclusion, clinical wastewaters were charged with a high proportion of multidrug resistant bacteria. Although most of these bacteria were eliminated during wastewater treatment, dissemination into surface waters is possible as single carbapenemase producers were still present in the effluent of the WWTP. Abstract : Hospital wastewaters are a source of resistant bacteria including extensively resistant high-risk strains with susceptibility to only one remaining antibiotic (colistin or tigecyclin or amikacin).